2020
DOI: 10.3390/microorganisms8040502
|View full text |Cite
|
Sign up to set email alerts
|

Biochar and Rhizobacteria Amendments Improve Several Soil Properties and Bacterial Diversity

Abstract: In the current context, there is a growing interest in reducing the use of chemical fertilizers and pesticides to promote ecological agriculture. The use of biochar and plant growth-promoting rhizobacteria (PGPR) is an environmentally friendly alternative that can improve soil conditions and increase ecosystem productivity. However, the effects of biochar and PGPR amendments on forest plantations are not well known. The aim of this study is to investigate the effects of biochar and PGPR applications on soil nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(41 citation statements)
references
References 61 publications
4
35
2
Order By: Relevance
“…Chloro exi is a Gram-negative bacteria that can potentially autotrophically metabolize through photosynthesis. This study found that after inoculation with PGPR, the relative abundance of Chloro exi in the rhizosphere soil was signi cantly negatively correlated with soil AN content (p < 0.05), which is similar to the results of Ren et al (Ren et al 2020) who found that after inoculation with biochar + PGPR, the soil nitrogen content increased, while the abundance of Chloro exi decreased. The cluster analysis results showed that the bacterial communities treated by strains A20 and A36 differed signi cantly from those treated with strains A13 and CK at the genus level, indicating that inoculation with strains A20 and A36 altered the soil bacterial community.…”
Section: Discussionsupporting
confidence: 90%
“…Chloro exi is a Gram-negative bacteria that can potentially autotrophically metabolize through photosynthesis. This study found that after inoculation with PGPR, the relative abundance of Chloro exi in the rhizosphere soil was signi cantly negatively correlated with soil AN content (p < 0.05), which is similar to the results of Ren et al (Ren et al 2020) who found that after inoculation with biochar + PGPR, the soil nitrogen content increased, while the abundance of Chloro exi decreased. The cluster analysis results showed that the bacterial communities treated by strains A20 and A36 differed signi cantly from those treated with strains A13 and CK at the genus level, indicating that inoculation with strains A20 and A36 altered the soil bacterial community.…”
Section: Discussionsupporting
confidence: 90%
“…Besides, PGPR may stimulate the synthesis of secondary metabolites that may increase the accumulation of potassium compounds in eucalyptus roots (Tinna et al 2020). Han et al (Ren et al 2020a) also reported that major increases in soil potassium content occurred in PGPR treatment over uninoculated control. Consistent herewith, we observed that soil available K content increased with PGPR applied in the soil.…”
Section: Effect Of Fs and Bf On Soil Nutrient Contentmentioning
confidence: 92%
“…Besides, Acidobacteria has been reported to be a predictor of soil health status and generally negatively correlated to soil quality, especially in relatively barren soil (Liu et al 2020). PGPR potentially decreased soil Acidobacteria phylum abundance in a eucalyptus seedling in south China (Ren et al 2020a). These ndings are consistent with the increase in soil quality after the application of BF in our study.…”
Section: Effect Of Fs and Bf On Soil Qualitymentioning
confidence: 99%
See 2 more Smart Citations